Physiological role of nitric oxide for regulation of arterial stiffness in anesthetized rabbits - Tatsuo Chiba; Kiyoshi Sakuma; Tetsuya Komatsu; Xin Cao; Megumi Aimoto; Yoshinobu Nagasawa; Kazuhiro Shimizu; Mao Takahashi; Yuichi Hori; Kohji Shirai; Akira Takahara (Elsevier, 2019)
We assessed effects of acetylcholine and Nω-Nitro-l-arginine methyl ester hydrochloride (l-NAME) on the cardio-ankle vascular index (CAVI), an indicator of arterial stiffness from origin of aorta to tibial artery, in halothane-anesthetized rabbits. Acetylcholine decreased the blood pressure, femoral vascular resistance and CAVI, whereas l-NAME did not affect the CAVI at a hypertensive dose. The acetylcholine-induced decrement of CAVI was completely suppressed by l-NAME. These results suggest that the arterial stiffness in rabbits may be independent from homeostatic production of nitric oxide, however, it can be decreased by large amounts of nitric oxide that are intrinsically produced by exogenously administered acetylcholine. Keywords: Arterial stiffness, Acetylcholine, l-NAME